Synthesis and Structural Characterization of N-Phenyl-5-norbornene-2,3-dicarboximide - Pei Liang, Zu; Li, Jian; Ru Pan, Xiao (Asian Journal of Chemistry, 2015)
The compound N-phenyl-5-norbornene-2,3-dicarboximide (C15H13NO2, Mr = 239.26) was synthesized and characterized by single crystal X-ray diffraction. The crystal belongs to monoclinic, space group P21/c, with a = 9.7534(13), b = 21.395(2), c = 12.0647(14) Å, b = 108.7020(10) °, V = 2384.6(5) Å3, Z = 8, Dc = 1.333 g/cm3, l = 0.71073 Å, μ(MoKa) = 0.089 mm-1, F(000) = 1008. The final refinement gave R = 0.0741, wR (F2) = 0.1676 for 4,199 observed reflections with I > 2a(I). The structure of the title compound comprises a racemic mixture of chiral molecules containing four stereogenic centres. X-ray diffraction analysis reveals that the cyclohexane ring tends towards a boat conformation, the tetrahydrofuran ring and the dihydrofuran ring adopt envelope conformations. The dihedral angles between the pyrrolidine-2,5-dione plane and the aromatic ring are 65.5 (2)° and 54.9 (2)°, respectively in the two molecules.